BIPHASIC THERMAL DEATH TIME CURVES AT HIGH AND ULTRAHIGH TEMPERATURES OF BACILLUS ‎SUBTILIS HU 1 SPORES - A. Al-Khayat , M.; I. Al-Horainy, J. (The Iraqi Journal of Veterinary Medicine, 1987)
Spores of Bacillus subtilis HU1 suspended in whole milk and /or distilled water subjected to high and ultrahigh temperatures ranging from 85 to 14°C. Resulting survivor and thermal death time (TDT) curves were shown to be non-linear for all temperatures investigated; convex survivor curves at most heating temperatures were observed. TDT curves observed in all studies were concave and biphasic. The z-value using milk as the menstruum were 57°C for heating temperatures of 121-140°C, and 20°C, for heating temperatures of 110-121°C. Distilled water as the menstruum yielded z-values of 58°C and 16°C for heating temperatures of 120-140°C and 110-121°C respectively.